Tipificação, habitus e interdependência: emblemas para um debate sociológico - Eliska Altmann (Ciências Sociais Unisinos)
In sociological theory one can enumerate different views that try to explain the social world and its agents or, more specifically, the relation between society and the individual. To discuss important methodologies and models of thought that found part of this field of Social Science, the article analyses, in the light of concepts dealt with by Alfred Schütz, Pierre Bourdieu and Norbert Elias, ideas such as naturalization of social life, relations between idea and action, and sociological interpretation of discourses.